Contrastive Analysis of Scientific Articles in the Area of Health - Rezende, Patrícia Almeida de (2012)
This paper compares scientific articles in six sub-areas of Health Studies. The articles were written in Portuguese and English by Brazilians or in English by native speakers of English. The analysis includes quantitative and qualitative differences in the use of hedging. The results suggest that Brazilians have a tendency to use a greater quantity and variety of hedges in English, quantitatively exceeding the hedging used by native speakers of English. It was also found that there are preferences in terms of the purposes with which these hedges are used in the two languages, with an inclination of Brazilians to use this resource mainly in the formulation of hypotheses.